Penafsiran Lafadz Rahmat dalam Tafsir Al Maraghi - Khoiriyah, Khoiriyah; Sulthoni, Akhmad; Amrulloh, Muhamad (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This research examines the interpretation of the term "Rahmat" (blessing) according to Ahmad Musthofa Al Maraghi in his Tafsir Al Maraghi. Tafsir Al Maraghi is one of the most renowned contemporary commentaries on the Quran, known for its detailed and profound approach to understanding the Quran and its interpretations. The study aims to analyze the concept of Rahmat as presented in Tafsir Al Maraghi, focusing on the interpretations of several relevant verses. The analysis reveals that in Tafsir Al Maraghi, the term "Rahmat" is interpreted as Allah's mercy towards His servants. This mercy manifests in various forms. Firstly, it is seen as the ultimate reward of paradise, which represents the highest benefit that believers can attain. Secondly, it is understood as the sending of Prophet Muhammad as a messenger with the message of Islam, aimed at bringing benefit to both the world and the hereafter. Thirdly, it is associated with the role of the Prophet Muhammad in guiding humanity, which is a fundamental aspect of his prophethood. Additionally, it is interpreted as paradise again, emphasizing the ultimate reward. Lastly, it is seen as seeking goodness, encouraging actions that lead to a sense of love and compassion among Muslims. This interpretation highlights the multifaceted nature of Allah's mercy in Islam as understood through Tafsir Al Maraghi.